Wind Systems in the Dead Sea and Footprints in Seismic Records - Lott, Friederike Franziska (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2017)
Atmospheric processes, such as wind, impact the ground motion of the earth and have the potential to induce strong broad-band noise in seismological records. In order to quantify the influence of wind on ground motion velocity joint seismological and meteorological measurements were conducted at the Dead Sea.Results reveal a pronounced impact of wind on seismological records. A methodology is presented to account for the dependency of PSD of ground motion velocity on the horizontal wind field.